Peranan Siniar sebagai Media Pembelajaran Sosiologi di Masa Pandemi - Martini Sugatri (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The purpose of this research is to know the role of podcast as a media to learn sociology in distance learning in the pandemic era at class XII IPS2 SMAN 1 Bantul semester 2 in academic year 2020/2021. The writing of this best practice belongs to a research which uses descriptive qualitative approach. The writer describes her best experience in solving the problem faced in the distance learning process in the pandemic era of covid-19. The subject of the research is the students of class XII IPS 2 in SMAN 1 Bantul in second semester in academic year 2020/2021 and the location of the research is SMAN 1 Bantul.The subject or the research consisits of 32 respondents. The data which are used are primary data taken by using google form. The data were collected through questionnaire. The data were analyzed by using data collection through google form. The steps which were used consisted of reducing the data available in google form, presenting the data in qualitative data and quantitative form, and drawing a conclusion. The result of the research of using of podcast as a media to learn sociology in the pandemic era is 100% of the respondents state that they like using podcast, 92,3% of the respondents state that they understand the material given through podcast, and 100% of the respondents state that podcast is easy to use as a media of learning. Besides, using podcast improves students’ interest and motivation to study in pandemic era. Using this Podcast is one of the solutions in distance learning in pandemic era of covid-19.